Membangun Bisnis Di Generasi Milineal Melalui E-Commerce - Rosyidi, Moh Ririn; Yusuf, Muhammad Hafidz; Suparno, Suparno; Izzah, Nailul; Rufaidah, Anik (Indra Institute Research & Publication, 2023)
This global situation in the fast and instant industrial era 4.0 will necessitate access to everything that can provide convenience to product users who don't need to leave the house, but can buy the products they need more easily with the help of IT. The advancement of information technology (IT) has created new opportunities for people's economic lives. People in the Al-Hadi Imaan Gresik Vocational School, the millennial generation, require in-depth knowledge of how to manage MSME marketing management by utilizing IT, specifically e-commerce by promoting and selling can be carried out throughout the world without time limits and at very high costs. lower than traditional promotions, so product/service offers can be made at any time. E-commerce can also generate.